Multiplicidade de soluções positivas para algumas classes de problemas elípticos em R2 com condição de Neumann - Oliveira, Elisânia Santana de (2012)
In this work, we prove the existence and multiplicity of positive weak solutions for some classes of elliptic problems in plane involving exponential growth of the Trudinger-Moser type with Neumann boundary condition. To do this, we use the method of sub and supersolution in combination with variational methods and the maximum principle.